1971
DOI: 10.2134/agronj1971.00021962006300030029x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Temperature Regimes on Growth Characteristics, Nutrition, and Grain Yield of IR22 Rice1

Abstract: The effects of soil and water temepratures of 15, 25 and 35 C on the growth, nutrition, and grain yield of rice (Oryza sativa L.) were studied at three stages of growth in the greenhouse. The dwarf variety IR22 was used as the test plant. Plants grown at greenhouse temperature were used as the control. Low temperatures at the early vegetative stage retarded the growth of shoots and roots. Compared with the control, higher soil temperatures accelerated the growth and development of the plants. A temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…In the present study, it was found that concentrations of N in the shoots and roots and N uptake in pearl millet increased considerably, whereas in maize, N uptake decreased at high temperature. High accumulation of N in pearl millet is quite parallel to what has earlier been reported in rice that N concentration in leaves increased markedly at high soil temperature (Bhattacharya and De Datta 1971). Thus, high thermotolerance of pearl millet could be related to its high N uptake and accumulation in the tissues (Mengel andKirkby 1987, Marschner 1995).…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, it was found that concentrations of N in the shoots and roots and N uptake in pearl millet increased considerably, whereas in maize, N uptake decreased at high temperature. High accumulation of N in pearl millet is quite parallel to what has earlier been reported in rice that N concentration in leaves increased markedly at high soil temperature (Bhattacharya and De Datta 1971). Thus, high thermotolerance of pearl millet could be related to its high N uptake and accumulation in the tissues (Mengel andKirkby 1987, Marschner 1995).…”
Section: Discussionsupporting
confidence: 57%
“…Treatment effects on tillering are more difficult to explain. Decreased tillering with drops in soil temperature has been observed before by other workers (2,4,10,34), though interactive response with low soil oxygen has not. Went (32,33) first proposed the idea of shoot dependence upon root-originated growth regulators which he called "caulocaline".…”
Section: Shoot Developmentsupporting
confidence: 49%
“…In addition, our study also found that soil moisture was negative related to soil temperature (Figure 4), and soil moisture of ST30-BR and ST40-BR was significantly higher than that of ST30-IR and ST40-IR, which might be a major factor for the lower soil temperature of ST-BR. Previous studies have reported that low soil temperature could inhibit germination and seedling growth of crop (Bhattacharyya and De Datta, 1971;Bollero et al, 1996;Chen et al, 2007). Barlow et al (1977) found that the changes of soil temperature by 1 °C had a significant influence on crop growth.…”
Section: Soil Temperaturementioning
confidence: 97%